The aerodynamic breakup and interactions of evaporating water droplets with a propagating shock wave - Huang, Z; Zhu, R; Davy, M (Springer, 2024)
The aerodynamic breakup physics of water droplets in shock–laden flows are investigated in this study. One-dimensional numerical simulations based on a hybrid Eulerian–Lagrangian approach are performed to study the interactions between propagating shock waves and monodispersed evaporating water droplets with breakup. Two-way coupling for the interphase exchanges of mass, momentum, and energy is considered for the two-phase gas–droplet flows. Parametric study on the droplet evaporation, motion, heating, and breakup dynamics is performed, through considering initial droplet diameters of 20–80 μm and incident shock Mach numbers (M0) of 1.3–4.0. The resultant initial droplet Weber numbers range between 10.0 and 4758.3, which cover the bag, bag-and-stamen, sheet stripping, and wave crest stripping breakup modes. The distance for breakup completion behind the transmitted shock and the resultant diameter all decrease with increased incident shock Mach number. When M0 ≥ 2.1, shock attenuation is also intensified with droplet diameter besides volume fraction under fixed droplet mass loading. Furthermore, net momentum transfer from the droplets to carrier gas (instead of in the opposite direction as extensively observed) occurs when M0 ≥ 2.1, mainly caused by the high temperature of post-shock gas and small diameter of broken droplets under strong incident shocks. A scale analysis shows that the momentum and energy transfer rates because of droplet evaporation have comparable magnitudes respectively to the counterparts from drag force and convective heat transfer. This is particularly true in the regions far off the shock front when M0 ≥ 2.1.